Analysis of drug use in university students in Quito (Ecuador) - Noroña Salcedo, Darwin R. (2022)
Introduction: The consumption of narcotic substances constitutes a serious social problem that affects the quality of life of those who consume it in a customary way. Knowledge of the agents that increase the probability of consumption is necessary to establish prevention criteria in higher education. Objective: Analyze the drug use of university students in relation to their socio-demographic variables and leisure activities. The study carried out had a quantitative approach with a non-experimental, cross-sectional, descriptive and correlational design. Method: A sample of 1755 students (752 women and 1003 men) were applied the ISTS Socioeconomic Survey and the EST-Diagnosis survey of the situation of consumption of alcohol, tobacco and other psychoactive substances in the university community of the Central University of the Ecuador, confirming the inference through the Chi square statistic and the odds ratio for the degree of association. Results: It was obtained that friendships, work conflicts and free time devoted to parties and leisure are associated with the consumption of tobacco and alcohol. On the other hand, factors such as the relationship with the family and the need for social acceptance were inferred with cocaine use. Conclusions: The nominal factors of gender, self-identification, monthly income and family responsibility obtained low association, and that the prediction of consumption is due to the influence of friends, labor conflicts, and acceptance needs.